THE EMERGENCE AND “CRISIS” OF THE MODERN CONCEPTION OF TIME AND ITS IMPLICATIONS FOR CONTEMPORANY HISTORIOGRAPHICAL AND PHILOSOPHICAL REFLECTION - FERREIRA, ANTONIO NELORRACION GONÇALVES (Outros Tempos: Pesquisa em Foco - História, 2019)
This article tries to address some of the main theoretical-methodological reflections (some with a more clearly political character) about the time in the field of the human sciences in the contemporaneity. The starting point is a brief outline of the modern conception of time. Since it is the constitution and "crisis" of this notion in its various unfoldings that appears as a condition of possibility of the reflections that will be addressed here, such as Reinhart Koselleck's "field of experience" and the "horizon of expectation", the redeemed time in Walter Benjamin and the becoming and the event in the unreconciled time of Gilles Deleuze. Keywords: Time. Modernity. Political.